Perancangan Digital Book Sejarah Kabupaten Boyolali - Guntur Adi Wijaya; Anwar, Ahmad Khoirul; Yulianto, Arif (JURNAL KEMADHA, 2023)
Abstract This final project is based on the lack of media knowledge about the history of the Boyolali district and exciting information for the public. Therefore, the ignorance about the history of Boyolali is fading over time. The design of this final project aims to reintroduce the history of Boyolali to the public, especially the millennial generation. Boyolali Regency is a regency located in the province of Central Java. The history of the establishment of Boyolali started with Sunan Kalijogo's preaching, so Ki Ageng Pandan Arang was aware of sangkan paraning dumadi. Thus he sincerely left his wealth and position in Semarang and wanted to travel Sufis from Semarang to Mount Jabalkat Bayat, Klaten Regency. Books are one of the print media that can be read repeatedly with more complex explanations and are more comfortable to read accompanied by interesting pictures in accordance with the theme of the book. This book can make an introduction or knowledge of information about the history of Boyolali district completely, so people understand what is being informed without any confusion. This book uses digital drawing techniques to make it more modern and attractive to the public, especially the millennial generation. Keywords: Design, Digital Book, History, Boyolali Regency.